Pengaruh Disparitas Gender Dalam Kepemimpinan Otentik Dan Mediasi Aktivitas Berbagi Pengetahuan Tacit Terhadap Kapabilitas Inovasi Redaktur - Detta Ammallia; Justine Tanuwijaya (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to use an authentic leadership style to explore whether male or female leadership of electronic editorial influences tacit knowledge sharing and innovation capabilities among the electronic editor. Data was collected through electronic questionnaires distributed to the population of electronic media editors in Jabodetabek using the convenience sampling method. A total of 120 participants completed valid questionnaires, then analyzed using the variant-based structural equation model (VB-SEM) and the Partial Least Square (PLS) method. The finding showed that authentic male leadership had a significant positive effect on editors' innovation capability, either directly or indirectly through tacit knowledge sharing. Meanwhile, women's authentic leadership has only a significant positive effect on editors' innovation capability through the mediation of tacit knowledge sharing. This study proposes a model for developing innovation capability among electronic media editors through authentic leadership as mediated by tacit knowledge sharing. Keywords: Gender Disparity, Authenticity and Mediation, Tacit, Editorial Innovation